Scripture first : biblical interpretation that fosters Christian unity - Oden, Daniel B.; Stark, J. David (Abilene Christian University Press, 2020)
"Scripture or tradition? The things of God or the things of men? It's easy, especially in the long shadow of the Reformation, to pit Scripture against tradition as enemies. After all, the goal of orienting one's faith to the Bible alone can be so alluring. But the Bible itself suggests there is a fundamental unity between Scripture and the tradition it embodies. Rightly appreciating this unity can set the stage for more faithful and robust engagement with Scripture. Today's polarized world needs thoughtful Christians who can reasonably consider their faith in light of what the Bible actually says. Scripture First examines where tradition comes from and how you can avoid trivial proof texting. Discover how the Old and New Testament can serve as a living and active resource for Christian life, and how God continues to lead his people as they engage his Word"--